2019
DOI: 10.1021/acs.oprd.9b00037
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzymatic Process for the Synthesis of (S)-2-Chloro-1-(2,4-dichlorophenyl) Ethanol

Abstract: Chloro-1-(2,4-dichlorophenyl) ethanol ( 3) is a chiral intermediate in the synthesis of luliconazole ((R)-E-1). Here, we report a novel biopreparation of 3 by bioreduction of 2-chloro-1-(2,4-dichlorophenyl) ethanone (2) using recombinant Escherichia coli expressing LK08, a ketoreductase mutant from Lactobacillus kefiri, as a biocatalyst. The reaction conditions for the biotransformation including pH, temperature, and concentration of isopropanol and NADP + , as well as the amount of recombinant E. coli cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, the conversion was found to decrease sharply when the substrate concentration was increased to 150 g/L. In our previous research, we found that the pH and temperature are essential for improving the enzyme activity and the cosubstrate equivalent is a key factor for the biocatalytic process. , Thus, the process optimization for the reaction conditions, including the pH, temperature, cosubstrate loading, and catalyst loading, was subsequently performed (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the conversion was found to decrease sharply when the substrate concentration was increased to 150 g/L. In our previous research, we found that the pH and temperature are essential for improving the enzyme activity and the cosubstrate equivalent is a key factor for the biocatalytic process. , Thus, the process optimization for the reaction conditions, including the pH, temperature, cosubstrate loading, and catalyst loading, was subsequently performed (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 For example, Wei et al reported an enzymatic process to synthesize (S)-2-chloro-1-(2,4-dichlorophenyl) ethanol, the chiral intermediate of luliconazole, by a novel KRED mutant, LK08, from Lactobacillus kefiri. 15 In 2004, Berendes Frank reported the bioreduction of ketone 4 to 5 using Saccharomyces cerevisiae, with a substrate concentration of 20 mmol/L (3.9 g/L) and an of ee 81% (the methyl ester derivative had an ee of 96%). 16 Herein, we aimed to develop a novel chemoenzymatic process for (S)-1-(pyridin-4-yl)-1,3propanediol to overcome the shortcomings of existing routes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first report, Chen and co‐workers developed a chemo‐enzymatic synthesis route to luliconazole, with the aforementioned bioreduction being employed to set the required stereochemistry (Scheme 22). [36a] Specifically, by screening an in‐house preserved library of ketoreductases, the authors found a Lk CR variant with five mutations (E67D, A94T, F147L, L199H, A202L) displayed best enzyme activity and stereoselectivity. After optimizing reaction conditions such as pH, temperature, as well as the amounts of isopropanol, NADP + and biocatalyst, the biotransformation was upscaled to 300 g. In the presence of 300 g/L wet E. coli cells, 0.1 g/L NADP + , and 70 % (v/v) isopropanol, 300 g/L of 2‐chloro‐1‐(2,4‐dichlorophenyl) ethanone ( 44 ) was completely reduced within 30 h at pH 6.0 and 35 °C, providing enantiomerically pure ( S )‐2‐chloro‐1‐(2,4‐dichlorophenyl) ethanol (>99 % ee) in 94.3 % yield with a HPLC purity of 99 %.…”
Section: Creation Of One Stereocenter Through Kred‐catalyzed Reductionmentioning
confidence: 99%
“…Wei et al. reported an enzymatic process for the synthesis of the chiral intermediate of luliconazole by the Lk ADH‐catalyzed bioreduction [8] . Hu et al.…”
Section: Introductionmentioning
confidence: 99%